Estimasi potensi kerugian ekonomi akibat wasting pada balita di indonesia - Renyoet, Brigitte Sarah; Nai, Hildagardis Meliyani Erista (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2019)
Background: Wasting cases for children under five are currently increasing, the high risk of malnutrition continues to increase so that it has an effect on increasing the prevalence of nutritional problems which results in decreased productivity.Objectives: To estimate the economic potential lost due to wasting in children under five.Methods: Descriptive research, by processing data from various related agencies which are all in the form of secondary data. Calculate using the Konig (1995) formula and a correction factor from Horton's (1999) study. The research activities are carried out starting July 2018 until September 2018.Results: Nationally based on the prevalence of wasting in children under five in 2013 amounting to IDR 1.042 billion - IDR 4.687 billion or 0.01% - 0.06% of the total GDP of Indonesia.Conclusion: The prevalence of high wasting problems can increase the potential for economic losses and affect the economy of a country especially in developing countries and one of them is Indonesia.